The Influence of Market Day Activities on the Value of Honesty in Children Aged 5-6 Years at One Roof Kindergarten Permata Hati Kembang Seri: Market day, nilai kejujuran - Hoiro, Pajar Sindi Latipatul; Habibi, Akhmad; Rosyadi, Akhmad Fikri (FKIP Universitas Jambi, 2025)
This study aims to determine the effect of market day activities on the honesty values ​​of children aged 5-6 years at Kindergarten Satu Atap Permata Hati Kembang Seri. The design used in this study is Pre-Experimental Design with the form of One Group Pretest Posttest Design. The population in this study amounted to 53 children and the sample in this study amounted to 25 children. The sampling technique used in this study was an observation sheet. The data analysis techniques used in this study were normality test, homogeneity test and hypothesis test. The results of the study indicate that there is an effect of market day activities on the honesty values ​​of children aged 5-6 years at Kindergarten Satu Atap Permata Hati Kembang Seri. This is evidenced by the t-test hypothesis test that t count (18.412)> t table (2.064) then Ho is rejected and Hi is accepted. Therefore, market day can be one of the activities developed in educational institutions, in order to train students' honesty. Keywords: Market Day, Honesty, Early Childhood, Kindergarten